IMPLEMENTASI METODE IQRA' KLASIKAL DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN SISWA SEKOLAH DASAR DI SDI DARUL FALAH GUMELAR LOR - Aina Al Mardliyah Nurhayati; Aprilla Annisatushshalihah; Arina Shulha Diynina; Susi Widianti; Zainab (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In reading the Qur'an, an effective learning method is required significantly improve student's abilities to read the Quran. The classical Iqra' method serve as a development and reference method approach that educators apply in the classroom. This research aimed to examine the impact of implementing the classical Iqra' method on enhancing student's Quran ability at SDI Darul Falah Gumelar Lor. This study uses a qualitative approach with descriptive methods. The findings suggest that the classical Iqra' method significantly enhances student's Quran reading abilities and is highly relevant for classroom application. Test results show that he most students (69.2%) demonstrate good hijaiyah letter recognition, 61.5% exhibit good makhraj accuracy, 50% apply basic tajwid correctly, and 57.7% display good reading fluency. Overall, the Quran reading ability of SDI Darul Falah Gumelar Lor students falls into the good category. These findings are expected to enhance the quality of student's reading the Quran, and both teachers and parents provide support to students.